Mitigation of Mycotoxin Content by a Single-Screw Extruder in Triticale (x Triticosecale Wittmack) - Breda Jakovac-Strajn; Janja Babič; Lato Pezo; Vojislav Banjac; Radmilo Čolović; Jovana Kos; Jelena Miljanić; Elizabet Janić Hajnal (Foods)
The aim of this study was to investigate the effects of extrusion processing parameters—moisture content (M = 20 and 24%), feeding rate (FR = 20 and 25 kg/h), and screw speed (SS = 300, 390 and 480 RPM), on the content of deoxynivalenol (DON), 15-Acetyl Deoxynivalenol (15-AcDON), 3-Acetyl Deoxynivalenol (3-AcDON), HT-2 Toxin (HT-2), tentoxin (TEN) and alternariol monomethyl ether (AME), using a pilot single-screw extruder in whole-grain triticale flour. The temperature at the end plate of the extruder ranged between 97.6 and 141 °C, the absolute pressure was from 0.10 to 0.42 MPa, the mean retention time of material in the barrel was between 16 and 35 s, and the specific energy consumption was from 91.5 to 186.6 Wh/kg. According to the standard score, the optimum parameters for the reduction of the content of analysed mycotoxins were M = 24 g/100 g, FR = 25 kg/h, SS = 480 RPM, with a reduction of 3.80, 60.7, 61.5, 86.5, 47.7, and 55.9% for DON, 3-AcDON, 15-AcDON, HT-2, TEN, and AME, respectively. Under these conditions, the bulk density, pellet hardness, water absorption index, and water solubility index of the pellet were 0.352 g/mL, 13.7 kg, 8.96 g/g, and 14.9 g/100 g, respectively.